2018
DOI: 10.1002/cdq.12119
|View full text |Cite
|
Sign up to set email alerts
|

Career Assessment and Counseling for STEM: A Critical Review

Abstract: Career counselors must continually enhance their knowledge and skills to assist clients contemplating careers in science, technology, engineering, and mathematics (STEM). Therefore, the authors review STEM disciplines and theory‐driven strategies for assisting diverse individuals to explore, enter, and persist in STEM careers. Appropriate use of career assessments can contribute greatly to this effort. To identify available measures for STEM‐focused domains and constructs, the authors conducted a journal conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 78 publications
(83 reference statements)
3
32
0
Order By: Relevance
“…Moreover, most of the STEM studies have focused on one or two STEM disciplines such as math, science, or engineering (e.g., [25][26][27][28]). In a recent review of studies published from 1983 to 2016, Rottinghaus, Falk, and Park [8] identified 17 STEM studies that used measures that were developed based on SCCT. Of these 17 studies, five focused on engineering, one on computing, eight on mathematics and science, one on science and engineering, and one on overall STEM domain vocations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, most of the STEM studies have focused on one or two STEM disciplines such as math, science, or engineering (e.g., [25][26][27][28]). In a recent review of studies published from 1983 to 2016, Rottinghaus, Falk, and Park [8] identified 17 STEM studies that used measures that were developed based on SCCT. Of these 17 studies, five focused on engineering, one on computing, eight on mathematics and science, one on science and engineering, and one on overall STEM domain vocations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, many researchers have applied various theoretical frameworks to investigate the factors that shape the individuals' STEM career interests. In much of the research on STEM careers, Social Cognitive Career Theory (SCCT) [7] has been the most widely used theoretical framework for empirical inquiry [8]. Empirical studies have shown that self-efficacy [9][10][11][12][13][14], interests [6,11,[15][16][17], course selection [14,16], STEM-related activities, school engagement [16,18], academic proficiencies, and familial background [16] are predictive of STEM-related career paths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, STEM self-efficacy beliefs are influenced by four primary resources of information: (a) mastery experience (or performance accomplishment; previous experience and performance), (b) vicarious experience (learning through observation), (c) social persuasion (or verbal persuasion; others' feedback and support), and (d) physiological reaction (emotional arousal; Bandura, 1977;Gist & Mitchell, 1992). Moreover, self-efficacy has been found to be predictive of academic-and career-related goals (Rottinghaus et al, 2018). Within the SCCT, students' choice to pursue or avoid STEM careers could be understood as the interaction among personal inputs, contextual variables, self-efficacy, and out-come expectations.…”
Section: Scctmentioning
confidence: 99%
“…Research also highlight the need for more attention in Science, Technology, Engineering and mathematics (STEM) literature on links between theories, research and practice [5,6]. The purpose of this study is to outline an integrated pedagogical framework using a games design intervention to generate interest and uptake of computer science by young people, increase their awareness of careers in the field, explore stereotypes and encourage diversity.…”
Section: Introductionmentioning
confidence: 99%